la Photographie, la ville et le paysage urbain au Chili. La recherche de l’image totale et la naturalisation de Santiago - Andrés Tellez (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article addresses the building of the city and its relationship to its natural boundaries by examining the role of photography as a cultural product within processes of a city’s construction, itself also considered as such. The relationship between the city of Santiago, Chile, and its natural context was a central theme for photographers between the 1930s and the 1970s, with its hill-lined urban grid and the Andes mountain backdrop, along with the rapid expansion it experienced during that time. Elements were thus put together in a variety of photographic approaches, ultimately contributing to Santiago’s naturalisation and leading to a collective acknowledgment of the city’s structure and material substance.